A FEW OBSERVATIONS ON THE BIOLOGY OF TACHYSURUS THALASSINUS RUPPELL FROM VERAVAL (GUJARAT) - RAJE, SADASHIV GOPAL (Journal of Indian Fisheries Association, 2015)
The length-weight relationship o.t; Ethalassinus differed in the sexes and, therefore separate equations were obtained; for males log W = -5.1728 4- 3.0495 log L; and for females log W = -5.7456 + 3.2798 log L. The spawning period of this species appears to be restricted to a short period from October to November. Fecundity has been found to range from 33 to 55 mature eggs in specimens of the size range 421-564nun, The sex ratio of males to females was 1.8:1. T.thalassintis is a bottom carnivore, crustaceans ranking first in food followed by fishes, molluscs and polychaetes.